PENGARUH PEMAKAIAN MATERIAL (DENGAN PENDEKATAN PERPUTARAN PERSEDIAAN) TERHADAP LABA PERUSAHAAN PADA PT PLN (PERSERO) DISTRIBUSI JAWA BARAT DAN BANTEN - -, Surtikanti (Jurnal Manajemen dan Keuangan, 2009)
Each company, it is often a problems whose appear at working capital management, any one of the element of working capital shaped is an inventory turn over. Inventory turn over whose to languid it can make any one of indication that company managerial too little optimal.The research findings and disccusion, it can be drawn a conclusion that inventory turn over has been influenced to profit company. This role is stated in calculatiof of coefficient of correlation as large 0.844; thus this relation pursuant is included into a âstrong relationâ category, and characteristic of that elationship isdirectional, it means if inventory turn over material is turn over with faster, than profit company will higher. Where its tcount 3,278 > ttable 3,182; therefore Ho lay in rejection area, and it means that Ha is accepted. The influence of inventory turn over to profit company is 78,2% and the remainding as 21,8%. And the rest explained by other factor for example operation cost, income, etc.Keywords : Inventory, inventory turn over material, profit.